Interval Observer for Discrete Periodic Time-varying Descriptor Systems⁎This work was partially supported by the National Natural Science Foundation of China (No. U1813216), the Natural Science Foundation of Guangdong (No. 2020A1515010334) and the Science and Technology Research Foundation of Shenzhen (JCYJ20170817152701660 and JCYJ20170412171459177). Issue 2 (2020) - Xu, Feng; Yang, Songlin; Wang, Xueqian; Wang, Ye
Abstract: This paper designs an interval observer for discrete linear periodic time-varying descriptor (LPTVD) systems. First, the discrete LPTVD system is transformed into a linear time-invariant (LTI) descriptor system by using a stacked form of periodic systems. Then, in order to reduce complexity, we further transform the equivalent LTI descriptor system into a minimal-order form. Finally, by using the obtained minimal-order implementation of the discrete LPTVD system, an interval observer is designed to estimate the system state interval at each step. At the end, an example is used to illustrate the effectiveness of the proposed results.